Cost effectiveness of a mail-delivered individually tailored physical activity intervention for Latinas vs. a mailed contact control - Larsen, Britta (Int J Behav Nutr Phys Act, 2015)
BACKGROUND: Physical inactivity is high in Latinas, as are chronic health conditions. There is a need for physical activity (PA) interventions that are not only effective but have potential for cost-effective widespread dissemination. The purpose of this paper was to assess the costs and cost effectiveness of a Spanish-language print-based mail-delivered PA intervention that was linguistically and culturally adapted for Latinas. METHODS: Adult Latinas (N = 266) were randomly assigned to receive mail-delivered individually tailored intervention materials or wellness information mailed on the same schedule (control). PA was assessed at baseline, six months (post-intervention) and 12 months (maintenance phase) using the 7-Day Physical Activity Recall Interview. Costs were calculated from a payer perspective, and included personnel time (wage, fringe, and overhead), materials, equipment, software, and postage costs. RESULTS: At six months, the PA intervention cost $29/person/month, compared to $15/person/month for wellness control. These costs fell to $17 and $9 at 12 months, respectively. Intervention participants increased their PA by an average of 72 min/week at six months and 94 min/week at 12 months, while wellness control participants increased their PA by an average of 30 min/week and 40 min/week, respectively. At six months, each minute increase in PA cost $0.18 in the intervention group compared to $0.23 in wellness control, which fell to $0.07 and $0.08 at 12 months, respectively. The incremental cost per increase in physical activity associated with the intervention was $0.15 at 6 months and $0.05 at 12 months. CONCLUSIONS: While the intervention was more costly than the wellness control, costs per minute of increase in PA were lower in the intervention. The print-based mail-delivered format has potential for broad, cost-effective dissemination, which could help address disparities in this at-risk population. TRIAL REGISTRATION: NCT01583140; Date of Registration: 03/06/2012; Funding Source of Trial: National Institute of Nursing Research (NINR); Name of Institutional Review Board: Brown University IRB; Date of Approval: 05/19/2009.